Associations Between Polymorphisms of the CSN1S1, CSN1S2, CSN2 and CSN3 Genes and Milk Composition Traits in Holstein Cattle - Ahmet Fatih Demirel; Bahattin Çak (Veterinary Medicine and Science)
ABSTRACT Background Caseins are the major proteins found in cow's milk. There are four known casein fractions: αS1‐casein, αS2‐casein, β‐casein and κ‐casein, encoded by the CSN1S1, CSN1S2, CSN2 and CSN3 genes located on the sixth chromosome of cattle. These genes are considered candidate genes in marker‐assisted selection. Therefore, it is essential to determine the relationship between these genes and quantitative characters. Objectives This study aimed to identify genotypes of CSN1S1, CSN1S2, CSN2 and CSN3 genes and investigate their effect on milk components with the PCR‐RFLP method in Holstein cattle. Methods The material of the study consisted of 519 Holstein cows that managed under intensive systems in Konya (n:189), Manisa (n:195) and Diyarbakır (n:135) provinces in Türkiye. Blood and milk samples from these cows were used in the study. The genetic structures of bovine CSN1S1, CSN1S2, CSN2 and CSN3 genes were examined by PCR‐RFLP in three Holstein cattle populations. A general linear model (GLM) was applied to analyse the effect of genotypic variants on phenotypic characters. Results Results indicated that milk solids‐non‐fat (SNF) (p < 0.01), protein (p < 0.05) and lactose (p < 0.01) percentages were significantly affected by the genetic variants of the CSN2 gene of cow in general population. CSN2 A2A2 genotype led to a significant increase in SNF, protein and lactose percentages by 0.14, 0.05 and 0.08 in comparison to other genotypes, respectively. Moreover, significant effect of the CSN1S1 BC (p < 0.05) and CSN3 AA (p < 0.01) genotypes on fat percentage were found in Konya province. Furthermore, a statistically significant genotype‐by‐environment interaction was identified in both the CSN1S1 (p < 0.05) and CSN3 (p < 0.01) genes in relation to milk fat content. Conclusions As a result, after increasing the number of studies that investigated the relationship between casein genes and milk traits and determined the genetic variation of CSN1S1, CSN2 and CSN3 genes of the Holstein cattle, these genes can be a strong genetic marker as marker‐assisted selection programme in early selection.